2015
DOI: 10.3389/fpsyt.2015.00050
|View full text |Cite
|
Sign up to set email alerts
|

Eyeblink classical conditioning and post-traumatic stress disorder – a model systems approach

Abstract: Not everyone exposed to trauma suffers flashbacks, bad dreams, numbing, fear, anxiety, sleeplessness, hyper-vigilance, hyperarousal, or an inability to cope, but those who do may suffer from post-traumatic stress disorder (PTSD). PTSD is a major physical and mental health problem for military personnel and civilians exposed to trauma. There is still debate about the incidence and prevalence of PTSD especially among the military, but for those who are diagnosed, behavioral therapy and drug treatment strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 163 publications
(179 reference statements)
1
18
0
Order By: Relevance
“…Specifically, lesions to the amygdala retard acquisition of classically conditioned eyeblinks, disrupt hippocampal activity in rats (Blankenship et al., 2005), and reduce the amplitude of the reflexive eyeblink (UR) in rabbits (Weisz et al., 1992). The amygdala has also been implicated both in the conditioned reflex modification as studied by Schreurs and colleagues in their rabbit model of PTSD as previously discussed (e.g., Schreurs and Burhans, 2015) and in avoidance learning in humans (Simmons et al., 2006; Mobbs et al., 2007; Samanez-Larkin et al., 2008; Straube et al., 2009; Suslow et al., 2009). As previously discussed, the effects of uncertainty in anxiety are thought to come about through enhanced hypervigilance in the amygdala (Grupe and Nitschke, 2013).…”
Section: Overlapping Neural Substrates Of Eyeblink Conditioning Avoimentioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, lesions to the amygdala retard acquisition of classically conditioned eyeblinks, disrupt hippocampal activity in rats (Blankenship et al., 2005), and reduce the amplitude of the reflexive eyeblink (UR) in rabbits (Weisz et al., 1992). The amygdala has also been implicated both in the conditioned reflex modification as studied by Schreurs and colleagues in their rabbit model of PTSD as previously discussed (e.g., Schreurs and Burhans, 2015) and in avoidance learning in humans (Simmons et al., 2006; Mobbs et al., 2007; Samanez-Larkin et al., 2008; Straube et al., 2009; Suslow et al., 2009). As previously discussed, the effects of uncertainty in anxiety are thought to come about through enhanced hypervigilance in the amygdala (Grupe and Nitschke, 2013).…”
Section: Overlapping Neural Substrates Of Eyeblink Conditioning Avoimentioning
confidence: 87%
“…In addition to eyeblink conditioning studies with rats and humans, a separate animal model of PTSD utilizing eyeblink conditioning involves modulation of the eyeblink reflex in rabbits (for review, see Schreurs and Burhans, 2015). In these studies, conditioning with a tone CS and periorbital eye shock US not only produced conditioned eyeblinks (CRs) but also produced a conditioning-specific reflex modulation (CRM) of the UR, specifically an increase in the amplitude and area of the eyeblink response to a periorbital shock; this CRM has been interpreted as reflecting hyperarousal (Burhans et al., 2008).…”
Section: A Rabbit Eyeblink Model Of Ptsdmentioning
confidence: 99%
“…Several reports indicate that EBC can be used to detect impairments in neuropsychiatric diseases, such as schizophrenia ( 11 14 ), Alzheimer’s disease [AD ( 15 17 )], progressive supranuclear palsy [PSP ( 18 )], and post-traumatic stress disorder [PTSD ( 19 )] EBC is significantly impaired by AD, relative to age-matched control subjects ( 15 , 17 ). There is the one report of EBC in patients with PSP, which indicates a severe impairment in acquiring EBC with trace intervals of 0, 300, or 600 ms ( 18 ); those authors concluded that the deficit was likely due to neuropathological changes in the cerebellar nuclei since other pathologies overlap with those of Parkinson’s disease (PD), which does not impair acquisition of EBC ( 20 ).…”
mentioning
confidence: 99%
“…There is the one report of EBC in patients with PSP, which indicates a severe impairment in acquiring EBC with trace intervals of 0, 300, or 600 ms ( 18 ); those authors concluded that the deficit was likely due to neuropathological changes in the cerebellar nuclei since other pathologies overlap with those of Parkinson’s disease (PD), which does not impair acquisition of EBC ( 20 ). The effects of PTSD on EBC are discussed by Schreurs and Burhans elsewhere in this volume ( 19 ). The EBC paradigm also reveals age-related learning impairments in humans ( 21 23 ), rabbits ( 24 ), and rats ( 25 28 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation